A STUDY OF THE EFFECT OF HOME ENVIRONMENT ON THE ACADEMIC ACHIEVEMENT OF CLASS IX STUDENTS (WITH REFERENCE TO SELECTED SECONDARY SCHOOLS OF NORTH DELHI) - Rinki Rani,; Sharma, Kavita (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Parents always expect their child to be number one in every field. Psychologists and psychiatrists have concluded on the basis of their surveys and studies that in most cases, those children who suffer from inferiority complex are those who do not get enough love, affection and intimacy in childhood. Psychologists and psychiatrists believe that if children can be encouraged towards excellence, their self-confidence is awakened. To solve the problem of a child, proper development of his family, better adjustment, good lifestyle and strong guidance are necessary. By receiving praise, children learn to respect their elders. The real meaning of making a secondary level student competent is to make him progressive and civilized so that his reasoning power can be developed. Family environment is the main determinant of the behaviour of any individual. It is a part of the inner life of the individual and is reflected in his behaviour. Various types of sanskars like religious, ideological, natural etc. act as motivating forces in the behaviour of the individual.